PRAKSIS EVALUASI PENDIDIKAN AKIDAH AKHLAK DI MADRASAH MANBA’UL FALAH SIDOREJO KECAMATAN PAMOTAN- REMBANG - Retnanto, Agus (QUALITY, 2015)
This study aims to (1) know the activeness of student learning in akidah akhlak aubject in Madrasah Manba’ul Sidorejo Falah Pamotan-Rembang, (2) knowthe teacher evaluation system in akidah akhlak subject in Madrasah Manba’ul Sidorejo Falah Pamotan-Rembang, (3)see the main effects and the impact of the implementation of the evaluation system accompanied to student achievement in akidah akhlak Education in Madrasah Manba’ul Sidorejo Falah PamotanRembang.This study is a qualitative research with naturalistic models and phenomenology approach. This approach carried out two phases: descriptive and evaluative stage. Descriptive stage is to explore the idea of IntegratedIslamic Education System, while the evaluative stage is descriptive-analytic approach, followed by comparison. The findings of this study are; Theactiveness of study at Madrasah Manba’ul Sidorejo Falah Pamotan-Rembang appear on the dimensions of the students subject: (1) lack of expression,thought, feeling, desire and courage to participate, (2) existence of effort and creativity, a sense of airy, and free to do anything. Akidah akhlak learningactiveness in Madrasah Manba’ul Sidorejo Falah Pamotan-Rembang which looks at the dimension of teachers are:(1) the efforts to foster and encourage the subject of students in increasing excitement and active student participation, (2) ability to carry out the functions and role of the teacher as an innovatorand motivator, (3) giving the opportunity to the students which essentially have individual differences, (4) ability to use a variety of teaching and learningstrategies as well as multimedia approach. On the dimension of the program: (1) the instructional objectives and concepts as well as the subject’s abilitylearners, (2) program that allows the development of the concept as well as the activity of the students subject, (3) a program that is not rigid in determiningthe methods and media are easily understood. On the dimensions of teaching and learning situation, such as (1) the teaching-learning situations that leadto social interaction and communication teacher-student in warmth and pleasant, (2) the excitement and joy of learning of the students subject.